2014
DOI: 10.3310/hta18340
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review, psychometric analysis and qualitative assessment of generic preference-based measures of health in mental health populations and the estimation of mapping functions from widely used specific measures

Abstract: This report should be referenced as follows:Brazier J, Connell J, Papaioannou D, Mukuria C, Mulhern B, Peasgood T, et al. A systematic review, psychometric analysis and qualitative assessment of generic preference-based measures of health in mental health populations and the estimation of mapping functions from widely used specific measures. Health Technol Assess 2014;18(34). This journal is a member of and subscribes to the principles of the Committee on Publication Ethics (COPE) (www.publicationethics.org/).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
193
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 210 publications
(205 citation statements)
references
References 226 publications
9
193
1
2
Order By: Relevance
“…In relation to the former point, it may be that the EQ-5D-5L instrument, which we have used to calculate QALYs over the period of follow-up, is insufficiently sensitive to clinically relevant changes in depression, as measured by the PHQ-9 or the primary outcome in the trial. A recent systematic review 390 of the validity and responsiveness of the EQ-5D in depression characterised the performance of the instrument as 'adequate' in distinguishing between known groups of patients, but it is less responsive to changes in depression over time. Nevertheless, it is not apparent that other generic measures of healthrelated quality of life would have offered greater responsiveness in calculating QALYs for the participants in the Healthlines depression trial.…”
Section: Discussion Of Depression Trial Cost-effectiveness Resultsmentioning
confidence: 99%
“…In relation to the former point, it may be that the EQ-5D-5L instrument, which we have used to calculate QALYs over the period of follow-up, is insufficiently sensitive to clinically relevant changes in depression, as measured by the PHQ-9 or the primary outcome in the trial. A recent systematic review 390 of the validity and responsiveness of the EQ-5D in depression characterised the performance of the instrument as 'adequate' in distinguishing between known groups of patients, but it is less responsive to changes in depression over time. Nevertheless, it is not apparent that other generic measures of healthrelated quality of life would have offered greater responsiveness in calculating QALYs for the participants in the Healthlines depression trial.…”
Section: Discussion Of Depression Trial Cost-effectiveness Resultsmentioning
confidence: 99%
“…These issues, however, are mainly directed at the suitability of OLS for predicting EQ-5D utility scores due its bi-or often tri-modal distribution [29] and the well documented ceiling effect of the instrument [30,31], which typically results in a concentration of observations at 1. A number of studies have found OLS to be appropriate when mapping to the SF-6D, often finding this method to demonstrate superior performance to alternatives such as Tobit, CLAD, two-part models and response mapping methods in this context [32][33][34]. The distribution of the SF-6D scores in both the estimation and validation data sets were therefore tested for normality in order to assess the appropriateness of OLS to model this particular relationship.…”
Section: Resultsmentioning
confidence: 99%
“…It has a sensitivity of 0.88 and a specificity of 0.89 and is well examined in patients with diabetes [30, 31]. The SF12 contains 12 items derived from the SF-36 that asks about the perceived mental and physical health in the past 4 weeks.…”
Section: Participants and Methodsmentioning
confidence: 99%